Manufacturer–retailer supply chain model with payment time-dependent discount factor under two-level trade credit. Issue 1 (31st December 2023) - Bhattacharjee, R.; Maiti, T.; Giri, B. C.
Abstract : It is usually observed in the marketplace that, for longer delayed payment, both the sales volume and the loss of interest in terms of opportunity cost turn up higher. On the other hand, for longer advanced payment, the sales volume appears lower but the earned interest appears higher. To balance between delayed and advanced payments, a discount factor that changes the wholesale price for different payment-term scenarios comes into play. In this paper, a single-manufacturer and a single-retailer supply chain model is developed where the manufacturer adopts a lot-for-lot policy for delivering the retailer's order quantity. The retailer offers a flexible payment time to customers. The market demand is assumed to be linearly dependent on the selling price. The discount factor which makes the difference between the two wholesale prices is taken as a function of payment time. The impact of advanced and delayed payments on the optimal payment time is discussed and analysed in a retailer-Stackelberg game structure. A numerical example is taken to exhibit the optimal results and perform sensitivity analysis.